Emisi Gas Rumah Kaca Sektor Pertanian di Kabupaten Tuban: Inventarisasi dan Potensi Aksi Mitigasi - Dhina Mustikaningrum; Kristiawan Kristiawan; Suprayitno Suprayitno (Department of Urban and Regional Planning, Diponegoro University, 2021)
The agricultural sector is one of the contributors to greenhouse gas emissions in Indonesia. The inventory of greenhouse gases in the agricultural sector is not only carried out on land management, but also in the livestock sub sector. Tuban Regency, East Java Province has great potential to contribute to greenhouse gas emissions in the agricultural sector considering that the area of agricultural land and livestock population in this area is very high. This study aims to carry out an inventory of greenhouse gas emissions in the agricultural sector and potential mitigation actions in the same sector. The results of the research are expected to provide input for the Tuban Regency Government in designing mitigation actions that are feasible to implement. The greenhouse gas emission inventory is calculated using Tier-1 IPCC (International Panel on Climate Change) 2006 guidelines by multiplying activity data with emission factors according to IPCC standards. Activity data used for calculating GHG emission comes from secondary data. Meanwhile, the mitigation options obtained from interviews with representatives of farmer groups in Tuban Regency .The results show that the greenhouse gas emissions of the agricultural sector in Tuban Regency in 2019 is 1,665.67 Gg CO2-eq with details of the agricultural sub-sector of 1,092.50 Gg CO2-eq and the livestock sub-sector of 573.17 Gg CO2-eq. In the agricultural sub-sector, Plumpang Subdistrict occupies the top position as a contributor to greenhouse gas emissions and Tuban Subdistrict is the lowest position. Meanwhile, in the livestock sub-sector, Kerek subdistrict occupies the top position in contributing to GHG emissions and the lowest is in Tuban subdistrict. Through the implementation of balanced fertilization mitigation options and the use of low-emission rice varieties, the GHG emission in Tuban Regency can be reduced by up to 156,43 Gg CO2-eq. Both options are selected by farmers because it is easier and cheaper without relying on others.